PREVALENCE OF PIROPLASMOSIS AMONG SHEEP IN THE CENTRAL PART OF IRAQ - M.A. Latif, B.; A. Al-Izzi, S.; S. Sultan, A. (The Iraqi Journal of Veterinary Medicine, 1987)
Out of 704 sheep examined from three provinces (Baghdad, Hilla and Diala) in the central part of Iraq, 323(45.88%) were infected with Theileria hirci, 80 (11.36%) with Anaplasma ovis and 19(2.70%) with Babesia motasi. The percentage of sheep infected with Th. Hirci was much higher (P < 0.01) than those with A. ovis and B. motasi. The rate of infection with Th. hirci and A. ovis but not B. motasi increased with advancing age. There was no significant (P>0.05) difference in the rate of infection between males and females